Cross-reactivity of two human IL-6 family cytokines OSM and LIF explored by protein-protein docking and molecular dynamics simulation - Du, Qingqing; Qian, Yan; Xue, Weiwei (Biochimica et biophysica acta. General subjects, 2021)
Oncostatin M (OSM) and leukemia inhibitory factor (LIF) are two important pro-inflammatory cytokines of the interleukin-6 (IL-6) family. The two cytokines mediated signaling was recently found to be closely associated with cancer and chronic inflammation, which represent promising therapeutic targets for the treatment of many solid tumors and inflammatory disease. As the most closely related members, cross-reactivity of them may result in undesired activation of off-target cells, leading to toxicity or lack of efficacy of the therapeutic effects. However, the mechanism of the cross-reactivity of OSM and LIF is not well understood. In this work, protein-protein docking, molecular dynamics (MD) simulations with explicit solvent and post endpoints binding free energy (BFE) analysis were carried out to further understand the structural and energetic principles of interactions between the two cytokines and the shared receptor LIFR. For the first time, the simulation given a computational model of OSM-LIFR interaction, and provided significant insights into the mechanism of OSM and LIF cross-react with LIFR. The identified common features shared by OSM and LIF bind to LIFR involving 10 “conserved” residues (90% similarity) distributed at the binding site III comprised of AB loop, BC loop and D helix. In addition, 11 shared residues were identified in LIFR contribute 77.85% and 84.63% energies for OSM and LIF binding, which play a critical role in the formation of the two cytokine-receptor complexes. Moreover, the “nonconserved” residues at the same position of cytokines such as Asp41 in OSM and Pro51 in LIF as well as the three residues (Glu338, Asn201 and Glu260) in LIFR were also discovered. These important information may facilitate the rational design of novel chemical or biological agents with less toxicity and improved efficacy. •A computational model of OSM-LIFR interaction was constructed for the first time.•The mechanism of OSM and LIF cross-react with LIFR were provided from per-residues interaction energy calculations.•The “conserved” and “nonconserved” residues at the same position of the two cytokines’ binding interface were discovered.